2018
DOI: 10.5194/bg-15-2819-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reviews and syntheses: Revisiting the boron systematics of aragonite and their application to coral calcification

Abstract: Abstract. The isotopic and elemental systematics of boron in aragonitic coral skeletons have recently been developed as a proxy for the carbonate chemistry of the coral extracellular calcifying fluid. With knowledge of the boron isotopic fractionation in seawater and the B∕Ca partition coefficient (KD) between aragonite and seawater, measurements of coral skeleton δ11B and B∕Ca can potentially constrain the full carbonate system. Two sets of abiogenic aragonite precipitation experiments designed to quantify KD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 61 publications
2
52
0
Order By: Relevance
“…This advance can help to resolve the problem of differing temporal and spatial scales among techniques used in coral calcification studies (Holcomb et al, ). Although geochemical (i.e., isotopic and elemental) analyses of coral skeletons are effective at deriving the carbonate system of the calcifying fluid (DeCarlo, Holcomb, & McCulloch, ; McCulloch, D'Olivo Cordero, Falter, Holcomb, & Trotter, ), such studies have been difficult to reconcile with alternative approaches based on inserting micro‐sensors into the coral calcifying fluid (Al‐Horani, Al‐Moghrabi, & De Beer, ; Cai et al, ; Ries, ; Sevilgen et al, ), or imaging the calcifying fluid of corals exposed to pH‐sensitive dyes (Comeau et al, ; Holcomb et al, ; Venn, Tambutte, Holcomb, Allemand, & Tambutte, ). Conversely, Raman spectroscopy can now be applied in vivo at temporal and spatial scales comparable to the micro‐sensor studies (Figure ), as well as to bulk powders for comparison to isotopic measurements (e.g., DeCarlo et al, , DeCarlo, Comeau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This advance can help to resolve the problem of differing temporal and spatial scales among techniques used in coral calcification studies (Holcomb et al, ). Although geochemical (i.e., isotopic and elemental) analyses of coral skeletons are effective at deriving the carbonate system of the calcifying fluid (DeCarlo, Holcomb, & McCulloch, ; McCulloch, D'Olivo Cordero, Falter, Holcomb, & Trotter, ), such studies have been difficult to reconcile with alternative approaches based on inserting micro‐sensors into the coral calcifying fluid (Al‐Horani, Al‐Moghrabi, & De Beer, ; Cai et al, ; Ries, ; Sevilgen et al, ), or imaging the calcifying fluid of corals exposed to pH‐sensitive dyes (Comeau et al, ; Holcomb et al, ; Venn, Tambutte, Holcomb, Allemand, & Tambutte, ). Conversely, Raman spectroscopy can now be applied in vivo at temporal and spatial scales comparable to the micro‐sensor studies (Figure ), as well as to bulk powders for comparison to isotopic measurements (e.g., DeCarlo et al, , DeCarlo, Comeau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A permanent shift in the physiology of coral biomineralization was also manifest as a gradual increase in B/Ca over time; a shift that typically indicates a decrease in dissolved inorganic carbon (DIC) or carbonate ion concentration ([CO 3 2− ]) in the calcifying fluid (T. M. DeCarlo et al, 2018;Holcomb et al, 2016). Similarly, U/Ca, considered to be influenced by [CO 3 2− ] (T. M. DeCarlo et al, 2015), showed a significant change in the inner-shelf coral.…”
Section: 1029/2019gc008312mentioning
confidence: 99%
“…The ability to upregulate pH ECF is critical for coral resilience to changes in ambient seawater pH 28 , therefore, lower internal pH and porous skeleton structure in GAs indicate that these lesions will be particularly susceptible to the increasing global threat posed by ocean acidification. Under such conditions, GAs must either increase energy ] ECF is calculated from δ 11 B and B/Ca using method of DeCarlo et al 32 . Benjamini-Hochberg false discovery rate 80 was used to adjust p-values for multiple comparisons.…”
Section: Carbonate Chemistry In the Extracellular Calcifying Fluid Dmentioning
confidence: 99%
“…Some elements, such as boron or its isotopes (δ 11 B), can serve as useful markers of calcification. For instance, δ 11 B varies according to internal pH (pH ECF ) [27][28][29] , and recent studies suggest that an all-important second carbonate system parameter can be calculated (thus allowing full carbonate system computation) using paired coral δ 11 B and B/Ca ratios to estimate internal carbonate ion concentration ([CO 3 2− ] ECF ) [30][31][32] . Collectively, the elemental and boron chemistries have the potential to reveal key differences in calcification processes, as well as differences in wider holobiont physiological and biochemical activity, between healthy and diseased corals.…”
mentioning
confidence: 99%
See 1 more Smart Citation